Data on the effects of repeated disturbances in aquatic bacterioplankton communities - Lindström, Eva S. (Uppsala University, 2017)
Disturbances are believed to be one of the main factors influencing variations in community diversity and functioning. Here we investigated if exposure to a pH press disturbance affected the composition and functional performance of a bacterial community and its resistance, recovery and resilience to a second press disturbance (salt addition). Lake bacterial assemblages were initially exposed to reduced pH in six mesocosms whereas another six mesocosms were kept as reference. Seven days after the pH disturbance, three tanks from each treatment were exposed to a salt disturbance.

See "Repeated disturbances affect functional but not compositional resistance and resilience in an aquatic bacterioplankton community" by Sjöstedt et al (2018) for furhter information.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för information om data och insamling.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on the effects of repeated disturbances in aquatic bacterioplankton communities
Repeated disturbances affect functional but not compositional resistance and resilience in aquatic bacterioplankton communities - supporting data
Keywords: plankton; plankton; Biology with specialization in Limnology; Biologi med inriktning mot limnologi; Ecology; Ekologi